Analisis Putusan Pengadilan Agama Jember Nomor Perkara: 465/Pdt.G/2021/PA.Jr - Yose Febrian Sianipar, Daniel; Bafadhal, Faizah (Zaaken: Journal of Civil and Business Law, 2023)
The phenomenon that occurs in the Jember Religious Court is that there is a case of divorce due to a homosexual husband which causes continuous disputes and quarrels, namely case number: 465/Pdt.G/2021/PA.Jr at the Jember Religious Court. The purpose of this study is to determine and analyze the basis for the judge’s consideration in decision number: 465/Pdt.G/2021/PA.Jr. The research in this writing is normative legal research. This research uses a statutory approach, conceptual approach, and case approach. Then analyzed using qualitative methods. The result of this research is the decision of the Jember Religious Court Case Number 465/Pdt.G/2021/PA.Jr with the legal basis of Article 19 letters (e) and (f) PP Number 9 of 1975 Jo. Article 116 letters (e) and (f). On the grounds of continuous disputes and quarrels, namely; Article 19 Letter (f) PP Number 9 of 1975 Jo. Article 116 Letter (f) of the Compilation of Islamic Law, the substance of the law has been proven. Then on the grounds of disability or illness on the part of the Defendant, namely; Article 19 Letter (e) PP Number 9 of 1975 Jo. Article 116 Letter (e) of the Compilation of Islamic Law is only based on the testimony of the plaintiff’s witness without any other supporting evidence such as a psychiatric diagnosis letter or a mental hospital certificate. This reason can be used because in the trial the Defendant abandoned his right to reject the Plaintiff’s argument so that it was decided by verstek. Abstrak Fenomena yang terjadi di Pengadilan Agama Jember terdapat perkara cerai gugat yang dikarenakan suami seorang homoseksual yang menyebabkan perselisihan dan pertengkaran secara terus menerus yaitu perkara nomor: 465/Pdt.G/2021/PA.Jr di Pengadilan Agama Jember. Tujuan penelitian ini Â untuk mengetahui dan menganalisis dasar pertimbangan hakim dalam putusan nomor: 465/Pdt.G/2021/PA. Penelitian dalam penulisan ini adalah penelitian hukum normatif. Penelitian ini menggunakan pendekatan perundang-undangan, pendekatan konseptual, dan pendekatan kasus. Kemudian dianalisis menggunakan metode kualitatif. Hasil dari peneltian ini adalah putusan Pengadilan Agama Jember Nomor Perkara 465/Pdt.G/2021/PA.Jr dengan landasan hukum Pasal 19 huruf (e) dan (f) PP Nomor 9 Tahun 1975 Jo. Pasal 116 huruf (e) dan (f). Pada alasan perselisihan dan pertengkaran secara terus-menerus yaitu; Pasal 19 Huruf (f) PP Nomor 9 Tahun 1975 Jo. Pasal 116 Huruf (f) Kompilasi Hukum Islam secara, substansi hukum telah terbukti. Kemudian pada alasan cacat badan atau penyakit pada diri Tergugat yaitu; Pasal 19 Huruf (e) PP Nomor 9 Tahun 1975 Jo. Pasal 116 Huruf (e) Kompilasi Hukum Islam hanya berdasarkan pada keterangan saksi penggugat tanpa adanya alat bukti pendukung lain seperti surat diagnosa psikiater ataupun surat keterangan rumah sakit jiwa. Alasan ini dapat digunakan dikarenakan dalam persidangan Tergugat menanggalkan haknya untuk menolak dalil Penggugat sehingga diputus secara verstek.